Impacto da formação docente internacional na produção científica: o caso da UFSCar - Reis, José Eduardo dos (2021)
The teacher education of Brazilian researchers abroad favors their insertion in international collaboration networks, through international scientific exchanges and partnerships, contributes to the success and quality of the performance of the Graduate Programs, generating results that benefit society. Several bibliometric indicators have been used in the performance evaluation of researchers, universities and countries, at national and international levels, such as impact and internationalization indicators, calculated from the citations received by the articles. The objective of the research was to investigate the relationship between the teaching abroad, represented by the completion of a doctoral course and / or postdoctoral internship abroad and the international collaboration, represented by the international co-authorships present in the institutional scientific output indexed in the database Web of Science (WoS). The research method used was the exploratory case study, and the case-unit, the Federal University of São Carlos (UFSCar). A bibliometric study was performed using the Lattes Platform and WoS as sources of information, and the sample analyzed comprised 12,787 bibliographic records and 1,915 Lattes Curricula of active teachers. As a result, a set of indicators was elaborated on the scientific output of teachers with and without training abroad and their impact on international scientific collaboration, through analysis of co-authorships. From the results obtained, through data enrichment, it was possible to ascertain the positive relationship between the training of doctoral or postdoctoral professors abroad with the formation of international networks and co-authorships, contributing to the impact of institutional scientific output. Initial considerations indicate that the results and discussion of this research can contribute to the improvement of initiatives including the development of indicators of scientific and technological production in Brazil, involving internationalization and, consequently, for the improvement of the National Graduate System, by providing a better understanding of international scientific collaboration, based on investigating the training and performance of Brazilian researchers.